Upacara Ngaben Simbolisasi Bhakti Terhadap Orang Tua - wayan Kari Arta (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
The Ngaben ceremony is one of the religious traditions in Hinduism. Ngaben is included in the type of pitra yadnya ceremony. The background of the research on the Ngaben ceremony symbolizing devotion to parents is to find out the motives of pratisentana, which are the background of the Ngaben ceremony. The Ngaben ceremony symbolizes devotion to parents. This research is qualitative research with a social theology approach. The data obtained in this study results from a field study, where the primary data is Hindus carrying out the mass cremation ceremony. In contrast, the secondary data is in the form of reference books, articles, and written documents found in libraries or other places related to research. The cremation ceremony carried out by Hindus is a form of actualization of Hindu teachings that can create social harmony. In addition, the Ngaben ceremony also provides awareness that the spirit of yadnya must be used as a reference in turning the wheels of the economy and upholding dharma.